Perbezaan Latar Belakang Pendidikan Agama Islam dan Kesannya Terhadap Tanggapan serta Keinginan Masyarakat Kedayan, Sabah Mengamalkan Amalan Tradisi - Ros Aiza Mohd Mokhtar; Che Zarrina Saari (2016)
Kedayan ethnic is one of the ethnic groups inhabiting Borneo island including Brunei, Sarawak and Sabah. All of them are Muslims who are believed to have been exposed to the spread of Islam during the Sultanate of Brunei at the end of the 15th century. As such, they are seen as those who understand Islam better than other ethnic groups on Borneo Island. Their awareness of Islamic education is also good. This can be seen in the numerous religious schools founded to teach Islamic education in Sipitang where Kedayan form the majority population. At the same time, Kedayan people also being associated with the uniqueness of their customs and traditions which they inherited for several centuries. Therefore, this study will focus on the differences in the attitude and intention of this community in performing their customs and traditions due to different levels of religious education. This study used a questionnaire distributed to 414 respondents. The findings of this study revealed high correlation between the attitude of Kedayan people toward customs and traditions and their intention to continue practicing their customs and traditions. Moreover, there was a statistically significant difference between attitude and intention of this community to practice their customs and traditions as far as different religious education backgrounds are concerned.